Comparing the clinical efficacy of resting and antihypertensive medication in patients of hypertensive urgency: a randomized, control trial. Issue 7 (July 2017) - Park, Sung Keun; Lee, Dong-Young; Kim, Won Joong; Lee, Sang Yoon; Park, Hyun Sun; Kim, Hae Won; Kim, Beom; Moon, Kyoung Hyoub
Abstract : Objective: Hypertensive urgency is defined as a severe elevation of blood pressure (BP) without target organ damage. In emergency room, hypertensive urgency has been conventionally managed by antihypertensive medication. However, there has been increasing concern for the safety of antihypertensive medication in hypertensive urgency. Thus, this study was to compare the clinical efficacy of resting and antihypertensive medication in managing hypertensive urgency. Methods: For 138 hypertensive urgency patients admitting in emergency room of Veterans Health Service (VHS) medical center, a single-center, randomized controlled trial was conducted. Hypertensive urgency patients were randomly allocated into one group out of resting group and antihypertensive medication (telmisartan) group at admission. We serially checked their BP every 30 min for 2 h, and evaluated change levels and decline of BP. Primary end point of the study was mean BP reduction from 10 to 35%. Additionally, change and decline of SBP and DBP were serially compared over 2 h. Result: The rate of individuals approaching primary end point was 68.5% in rest group and 69.1% in medication group ( P  = 0.775). The change levels of BP for 2 h had no significant difference in SBP ( P  = 0.882) and DBP ( P  = 0.411) between resting group and medication group. The decline of BP after 2 h also did not show any statistical difference in both SBP ( P  = 0.065) and DBP ( P  = 0.032) between both groups. Conclusion: There was no significant difference between resting and antihypertensive medication in reducing BP of hypertensive urgency patients. This finding suggests the clinical efficacy of resting in managing hypertensive urgency.